2004
DOI: 10.1007/s11282-004-0014-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the temporomandibular joint: a study of inter- and intraobserver agreement

Abstract: Objective. The purpose of this study was to estimate the inter-and intraobserver agreement for interpreting magnetic resonance (MR) images of the temporomandibular joint (TMJ). Methods. The study was based on MR images of 30 TMJs. The images were interpreted by seven observers for disk configuration, disk position, joint fluid, bone marrow changes, and diagnosis. The observers were not calibrated. Kappa statistics were used. Results. The kappa values were, for interobserver agreement of disk configuration, 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
4
9
0
Order By: Relevance
“…17 It seems that the diagnosis ''anterior disc displacement without reduction'' reached the highest kappa values and agreements between observers in different publications. 8,13,[15][16][17] In 80% of the cases the five observers agreed on the diagnosis of the disc in the sagittal plane, a finding that is similar to our results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…17 It seems that the diagnosis ''anterior disc displacement without reduction'' reached the highest kappa values and agreements between observers in different publications. 8,13,[15][16][17] In 80% of the cases the five observers agreed on the diagnosis of the disc in the sagittal plane, a finding that is similar to our results.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with the findings of Takano et al, 15 Widmalm et al, 16 Butzke et al 17 and Schmitter et al 8 However, better agreement of the disc shape was found by Tasaki et al 10 One way of increasing the agreement between observers is to reduce the number of categories. This was proposed by Takano et al 15 regarding the finding of joint effusion, and in our study, if the finding of joint fluid was dichotomized to ''yes'' or ''no'', the observer agreement would increase to 80%. Therefore, we propose that the criteria described by Ahmad et al 5 are changed for joint effusion to be stated as present or not.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study has shown that when the examiners were not calibrated, the kappa values for inter-examiner agreement on TMJ disc position or configuration were poor. 77 These issues were addressed in our study, as the radiologists were calibrated and used clearly defined image analysis criteria. In detecting effusion, a study reported poor reliability (k = 0.36) for noncalibrated examiners; 77 however, the calibrated examiners in our study had good reliability (k =0.64).…”
Section: Discussionmentioning
confidence: 99%
“…77 These issues were addressed in our study, as the radiologists were calibrated and used clearly defined image analysis criteria. In detecting effusion, a study reported poor reliability (k = 0.36) for noncalibrated examiners; 77 however, the calibrated examiners in our study had good reliability (k =0.64). Our data suggest that the image analysis criteria developed for the RDC/TMD Validation Project and calibrated examiners led to more reliable interpretation than other reports.…”
Section: Discussionmentioning
confidence: 99%